PENGARUH STRATEGI KONTEN MARKETING PRODUK BITTERSWEET BY NAJLA DALAM KEPUTUSAN PEMBELIAN DI SURABAYA - Gracesita, Maria (Universitas Widya Kartika Surabaya, 2024)
The development of technology is becoming more sophisticated, and the acceleration of theworld is increasing over time, including in the field of online marketing. This research aims toexamine the influence of the marketing strategy of Bittersweet by Najla on purchasing decisionsin Surabaya. The population and sample in this study are all Najla consumers in Surabaya whomade purchases and consumed the products during a certain period. The research method usedis a mixed method, which combines quantitative and qualitative approaches. The researchvariables consist of independent variables: influencer (X1), content advertisement (X2), brandimage (X3), and the dependent variable of purchasing decision (Y). The data analysis techniqueused is multiple linear regression. The results of the study prove that influencers and brandimage do not have a significant influence on purchasing decisions. Meanwhile, contentadvertisements have a significant influence on purchasing decisions. This shows that thecombination of content used by Najla, which includes calls to interact, persuasion, and activeengagement, is able to elicit responses from consumers to build a close relationship withBittersweet by Najla. This active content activity is able to have a positive and significant impacton purchasing decisions. As a result, content advertisements have a significant effect on thepurchasing decisions of Bittersweet by Najla’s dessert box products